HUKUM KEPERAWATAN: MENGATUR TUGAS, TANGGUNG JAWAB, DAN HAK PERAWAT DALAM MEMBERIKAN PELAYANAN KESEHATAN BERKUALITAS - Hotmaria Hertawaty Sijabat (INTELIGENSIA MEDIA, 2025)
The nursing profession is a vital component of the healthcare system, not only providing patient care but also ensuring the achievement of service quality standards oriented towards patient safety and welfare. This study aims to analyse in depth the legal regulations governing the duties, responsibilities, and rights of nurses, as well as to examine the implementation of nursing law in realising quality health services in Indonesia. The method used is a literature review with a normative juridical approach, namely examining legislation, health law literature, and relevant previous research results. The results of the study show that nursing law, as regulated in Law Number 38 of 2014 concerning Nursing, serves as a legal basis to ensure legal certainty and protection for nurses in carrying out their profession. However, implementation in the field still faces obstacles in the form of low legal awareness, weak supervision, and suboptimal professional guidance. Therefore, it is necessary to strengthen the synergy between the government, professional organisations, educational institutions, and health institutions in building a legal culture oriented towards ethics, accountability, and professionalism. Consistent strengthening of nursing law is believed to be capable of improving the quality of health services and providing balanced protection for nurses and patients.